The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jbiomech.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Associations between in-vivo glenohumeral joint motion and morphology

Abstract: Joint morphology has a significant influence on joint motion and may contribute to the development of rotator cuff pathology, but the relationships between glenohumeral joint (GHJ) morphology and in-vivo GHJ motion are not well understood. The objectives of this study were to assess measures of joint morphology and their relationship with in-vivo joint motion in two populations: shoulders with intact rotator cuffs (n=48) and shoulders with rotator cuff pathology (n=36, including 5 symptomatic tears, 9 asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…7 In vivo joint motion and various morphologic parameters were also tested for correlation, but only CSA proved to be significantly higher in subjects with pathologic rotator cuffs than in controls. 31 Two biomechanical cadaveric experiments confirmed the specific effect of AI and GI on glenohumeral joint stability, as well as their relation with CSA. 15,28 Despite the radiologic observations and recent in vitro simulation studies, the biomechanical rationale between GI, AI, and CSA on the one hand and glenohumeral osteoarthritis and rotator cuff tendon tears on the other hand is not completely understood yet.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…7 In vivo joint motion and various morphologic parameters were also tested for correlation, but only CSA proved to be significantly higher in subjects with pathologic rotator cuffs than in controls. 31 Two biomechanical cadaveric experiments confirmed the specific effect of AI and GI on glenohumeral joint stability, as well as their relation with CSA. 15,28 Despite the radiologic observations and recent in vitro simulation studies, the biomechanical rationale between GI, AI, and CSA on the one hand and glenohumeral osteoarthritis and rotator cuff tendon tears on the other hand is not completely understood yet.…”
mentioning
confidence: 61%
“…GI and AI were associated with rotator cuff tendon tears and glenohumeral osteoarthritis. 17,27,29,31,39,41 In this study, we used a biomechanical shoulder model to evaluate the relative effects of these 2 different anatomic parameters on upward translation of the humeral head and glenoid articular cartilage strain. Assuming the hypothesis that humeral head translation and articular cartilage strain are mechanically related to rotator cuff tendon tears and glenohumeral osteoarthritis, respectively, the model predictions confirmed all previously reported biomechanical and clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…The glenoid shape is important in normal shoulder kinematics and dynamics. Peltz et al 11 found that glenoid morphology has a substantial influence on glenohumeral joint (GHJ) motion, with a more superiorly oriented humeral head during abduction in flatter and less conforming glenoids. To recreate normal kinematics and dynamics, the current axiom in surgery skews toward reconstructing the anatomy to the premorbid state.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 To the contrary, an in vivo study quantifying glenohumeral joint motion found a more inferior orientation of the humeral head during abduction in normal shoulders with a higher CSA. 11 Although it has been subject to debate and thorough biomechanical evidence is still missing, morphologic differences of the coracoacromial (CA) arch have been associated with overuse pathologies such as shoulder impingement syndrome. Anatomic factors that might contribute to this syndrome include shape variation of the acromion, variation in acromial slope, prominent bony spurs on the inferior aspect of the CA-joint or CA-ligament [12][13][14][15][16] and morphologic differences of the coracoid process.…”
mentioning
confidence: 99%
“…When thoracohumeral abduction exceeds 90°, a higher CSA leads to inferior translation of the humeral head in normal shoulders as shown in an in-vivo model 44. This counterintuitive effect may be explained by a downward directed lever arm through the surrounding soft tissue that is pressed into the acromial arch during deltoid activity in abduction above 90°.…”
Section: Pathology Of Rotator Cuff Tendons and Musclesmentioning
confidence: 92%